IMPLEMENTASI KERJASAMA INDONESIA – INGGRIS DALAM KERANGKA MULTISTAKEHOLDER FORESTRY PROGRAMME 3 (MFP 3) TERHADAP PENINGKATAN PRODUK KAYU INDONESIA - Antoko Ridho; Laode Muhamad Fathun; Mansur Juned (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2019)
This study discusses the Implementation of Indonesian and British Cooperation in the Elite Cooperation of Multistakeholders Forestry Program. In this collaboration Indonesia and the UK have rules regarding the existence of illegal logging in Indonesia. Indonesia's policy is Certification of Timber Legality Verification. The United Kingdom or the European Union has a policy that is Law Enforcement and Forest Law Governance (FLEGT). This research was conducted on the Implementation of MFP 3 on Indonesian wood products. The Thinking Framework of this model uses the theory of International Cooperation, the Concept of Sustainable Development. This research uses descriptive method with a qualitative approach. The collaboration between Indonesia and the UK produces several impacts on Illegal Logging and timber production and forest management in Indonesia in 2014-2016.